THE URGENCY OF ISLAMIC GUIDANCE AND COUNSELING TO SANTRI IN PESANTREN FROM THE PERSPECTIVE OF MASLAHAH DARURIYYAH - Reza Mina Pahlewi (Al-Tazkiah Jurnal Bimbingan dan Konseling Islam, 2024)
The purpose of this study is to find out why Islamic Guidance and Counseling to Santri at Pesantrens is urgent from the perspective of Maslahah Daruriyyah. Pesantrens, like other educational institutions, cannot be separated from the problems of their santris. The problems that are often faced by santris in participating in activities at Pesantrens include problems related to personal life, social life, learning, and self-adaptability to the pattern of pesantren life. Each of these problems has different characteristics and patterns so that different solutions are needed according to their respective characteristics. Islamic Guidance and Counseling is the provision of assistance to individuals to live in harmony with the provisions and instructions of Allah so that they can achieve happiness in life in this world and in the hereafter. Thus Islamic Guidance and Counseling is a guidance process like any other guidance process, but in all its aspects based on Islamic teachings, meaning based on the Qur'an and the Sunnah of the Prophet. Islamic Guidance and Counseling can be used to enforce the Objectives of Islamic Law. Islamic Guidance and Counseling can be used as an approach to meet the objectives of Islamic Law, that is to provide protection. The details of this protection are explained in fiqh books, but the essence is only five, namely: Protection of religion (Hifdz Ad-Din) Protection of the soul (Hidfz An-Nafs) Protection of reason (Hidfz al-Aql) Protection of offspring (Hidfz An-Nasl) Protection of wealth (Hidfz Al-Mal)